2015
DOI: 10.1039/c5ay00513b
|View full text |Cite
|
Sign up to set email alerts
|

Determination of very low amounts of free copper and nickel ions in beverages and water samples using cloud point extraction assisted by silver nanoparticles

Abstract: Silver nanoparticles (AgNPs), functionalized with the sodium salt of 2-mercaptoethanesulfonic acid (MESNA), can be used in a cloud point extraction process with Triton X-114 to transfer low amounts of copper and nickel ions to the surfactantrich phase. Both metals are then measured in the coacervate by electrothermal atomic absorption spectrometry. For a 20 mL aqueous phase containing a low concentration (100 μg L -1 ) of the functionalized AgNPs and 0.15% Triton X-114, an enrichment factor of 510 is achieved.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This procedure allows us to transfer tiny amounts of metal ions into the ML. The D. L. is 2.4 and 2.1 ng/L for Cu(II) and Ni(II), respectively [75]. On the other hand, for extraction, Cr(III) and Cr(VI) used unmodified AgNPs as a support carrier with the present Triton X-114 [76].…”
Section: Researchers In Chemistry Have Difficulty Determiningmentioning
confidence: 99%
“…This procedure allows us to transfer tiny amounts of metal ions into the ML. The D. L. is 2.4 and 2.1 ng/L for Cu(II) and Ni(II), respectively [75]. On the other hand, for extraction, Cr(III) and Cr(VI) used unmodified AgNPs as a support carrier with the present Triton X-114 [76].…”
Section: Researchers In Chemistry Have Difficulty Determiningmentioning
confidence: 99%
“…The recoveries ranged from 73.8% to 105.4% with RSDs <10.4%. Lopez-Garcia et al 38 showed that Ag NPs, functionalised with 2-mercaptoethanesulfonic acid, could be used to assist the transfer of Cu and Ni at low concentrations from the aqueous to the surfactant-rich phase (coacervate) during CPE. The authors optimised the procedure and ascertained that the pH range 3.0-3.5 was required with heating to 40 C for 10 min.…”
Section: Collection Storage and Preliminary Preparationmentioning
confidence: 99%
“…There was many application for solvent extraction to separation and determination metal elements as cations or as anions and applicable their methods for determination these elements in different samples after determination optimum condition [4][5][6][7][8][9][10] .And in preferential research involved separation and extraction Lanthanum(III) by joined cloud point with salvation [11] .By application Onium method for separation and spectrophotometric determination of Co(II) joined with cloud point extraction methodology [12] . Extracted many metal ions by solvent extraction methods [13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%